2023
DOI: 10.4103/abr.abr_18_22
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of four techniques to administer laryngeal mask airway

Abstract: Background: Laryngeal mask airway (LMA) plays a crucial role in the field of modern anesthesia. There are different techniques to administer LMA. Here we aimed to compare the four methods of standard, 90° rotation, 180° rotation, and thumb placement in LMA mast placement. Materials and Methods: This is a clinical trial that was performed on 257 candidates of elective surgical operations requiring general anesthesia. All patients were categorized into four groups of LMA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Their findings indicated that the 90°r otation method had a significantly higher success rate and a lower failure rate for successful mask placement compared to the other 3 methods. However, no significant differences were reported between the 4 groups of patients regarding their initial vital signs (9).…”
Section: Introductionmentioning
confidence: 81%
“…Their findings indicated that the 90°r otation method had a significantly higher success rate and a lower failure rate for successful mask placement compared to the other 3 methods. However, no significant differences were reported between the 4 groups of patients regarding their initial vital signs (9).…”
Section: Introductionmentioning
confidence: 81%